“Instant enemies” and “Instant allies” in the U.S. and Taiwan: a LIWC analysis - Cheng, Wen; Ickes, William; Park, Anna; Wu, Hui-Ju; Riani, Yuyun Agus (Frontiers in Communication, 2023)
An online survey was used to collect participants' retrospective accounts of an encounter with an "instant enemy" and an encounter with an "instant ally” in samples of 262 American and 250 Taiwanese respondents. Using software that measured the relative use of various word categories, we examined ingroup/outgroup differences and cultural differences in the experience and perception of an “instant enemy” and an “instant ally.” With regard to ingroup/outgroup differences, we found that inclusive and positive emotion words were used more frequently to describe the instant ally encounters, whereas exclusive and negative emotion words were used more frequently in reports of the instant enemy encounters. We also found that our respondents’ descriptions of instant ally encounters were more likely to be put into a context defined by words related to leisure, work, and space, whereas their descriptions of instant enemy encounters were more likely to ignore the context and focus instead on what type of person the instant enemy was, as defined by more personal pronouns and words denoting specific categories of humans. With regard to cultural differences, we replicated previous findings indicating that Asian respondents tend to have thoughts and perceptions that are more holistic and integrated than those of Western respondents, as indicated by more words related to cognitive and affective processes, insight, and awareness of causation. Viewed collectively, the findings make a strong case that word-category usage can reveal both well-established and novel findings in comparisons of individuals from different cultures.